An evaluation framework for new tests that predict progression from tuberculosis infection to clinical disease. Issue 4 (25th October 2018) - Kik, Sandra V.; Schumacher, Samuel; Cirillo, Daniela Maria; Churchyard, Gavin; Boehme, Catharina; Goletti, Delia; Rangaka, Molebogeng X.; Denkinger, Claudia M.; Lienhardt, Christian; Gilpin, Christopher; Matteelli, Alberto; Cobelens, Frank
Novel accurate tests are needed that identify individuals infected with Mycobacterium tuberculosis who have incipient disease and are likely to develop clinical tuberculosis (TB) in the near future to allow for targeted preventive treatment beyond the current risk groups. Recently, a target product profile was developed that outlines the minimal and optimal characteristics for such an incipient TB test. We describe an evaluation framework for generating evidence to inform the development of policy guidance for the use of such a new test by the World Health Organization. Two research objectives are addressed. 1) The predictive ability of an incipient TB test should be assessed in clinical evaluation studies that include the intended target population and follow-up of sufficient duration to observe whether individuals do or do not progress to clinical TB disease. 2) Studies are needed to evaluate the test under routine programmatic conditions and measure its impact on patient- or health-system-important outcomes. For both research objectives, study designs, methods and analysis are described, with the intent to inform the clinical development plans of test manufacturers, researchers and funders. An evaluation framework to evaluate new tests that predict development of clinical tuberculosis http://ow.ly/zVZH30kZEsU